Experimental characterization of tearing fracture in soft gels - Paarthebun, K. (2017)
Soft gels have a diverse range of applications in today’s world. It has been increasingly adopted in tissue engineering, pharmaceutical and robotics. As the reliance on soft material grow rapidly, understanding the mechanical behaviour of this material will further equip the engineers, with knowledge of mechanical stability, when designing soft gel incorporated products. This formal report will focus on experimentally investigating what effects the various parameters (initial crack length, width, breadth and concentration) have in mode III tearing displacement , initiation of crack propagation and complete fracture in agar test specimens. Experimental data are attached in the Appendix section and the results are graphically analysed in detail. Results are used to draw useful relationships. This correlation can be beneficial to the industrial applications of soft materials.